Chemical characterization of Echium plantagineum seed oil obtained by three methods of extraction. Issue 12 (28th November 2021) - Carlini, Giovanna Calixto Garcia; Roschel, Gabriela Grassmann; Ferrari, Roseli Aparecida; Alencar, Severino Mathias; Ota, Helton Cherubim; da Silveira, Tayse Ferreira Ferreira; Castro, Inar Alves
Abstract : Abstract: Echium seed oil has been considered an important alternative source of omega 3 fatty acids (n‐3 FA) for human consumption. Considering the oxidative instability of n‐3 FA richer oils, the objective of this study was to determine the chemical and sensory parameters of the oil obtained from Echium plantagineum seeds obtained by three extraction methods (hydraulic press: HYD; continuous screw press: PRESS; and solvent technique: SOLV). Stearidonic acid (C18:4, n3), the most important n‐3 FA present in the oil, changed from 12.5% to 12.7%. Regarding the minor compounds, PRESS sample showed the highest concentration of gamma‐tocopherol (782.24 mg/kg oil), while SOLV samples presented the highest amount of β‐sitosterol (73.46 mg/100 g) with no difference of campesterol concentration (159.56 mg/100 g) among the samples. Higher values of total phenolics (19.65 mg GAE/kg oil) and β‐carotene (34.83 mg/kg oil) were also found in the SOLV samples, suggesting the influence of hexane in the extraction of these bioactive compounds. High resolution mass spectrometry identified caffeic acid and its derivatives as the main phenolic compounds present in the echium oil. PRESS sample showed the best oxidative stability as measured by PV (0.61 mmol/kg oil) and malondialdehyde (173.13 µmol), probably due to faster time of processing compared to HYD and SOLV samples. Our data showed that the extraction method changed the chemical composition of the minor compounds in the echium oil, but these alterations did not reduce its nutritional quality or sensory acceptability. Practical Application: Echium oil represents a great potential source of omega 3 fatty acids, but there is not enough information about its oxidative stability and chemical composition, especially toward minor compounds. Our study characterizes echium oil composition obtained from three extraction methods, contributing to amplify the technical information about this important alternative oil for human consumption.